The sum of three times a number and 8 is –22. What is the number?1.)–10
2. )10
3. ) –5
4.) 5
Can someone help please.

Answers

Answer 1
Answer: If you subtract 8 from -22 and then divide by 3 you get the answer, -10
Answer 2
Answer: Let's take this phrase by phrase.

sum of three times a number and 8 = 3x + 8
Whenever there is a term mentioned without a definite value, we can represent it with a variable. In this case, I represented the number with "x".
is -22 means =-22
What equals -22? The sum of three times a number and 8 equals -22.
3x + 8 = -22
Subtract both sides by 8
3x = -30
x = -10

Final Answer: 1) -10

Related Questions

A rectangle measure 11cm by 30cm.What is its area
Sum of the ages of a father and the son is 40 years. If father's age is 3 times that of his son, then father's age is ________ * 2 points 35 40 30 45
A publisher claims that the average salary paid at its company is $37,500 but it could differ as much as $4500. Write and solve an absolute value inequality to determine the range of salaries at this company.|x − 37500| ≤ 4500; The salaries range from $33,000 to $42,000 |x − 37,500| ≤ 4500; The salaries are less than $33,000 or greater than $42,000. |x − 37500| ≥ 4500; The salaries range from $33,000 to $42,000 |x − 37,500| ≥ 4500; The salaries are less than $33,000 or greater than $42,000.
Please help me with this question! :)
Hey guys I'm pretty sure I got the first two questions but if I didn't can you help me and I need help with the last two questions.

When (2x-3)^2-3 is subtracted from 5x^2 the result is?

Answers

(2x-3)² - 3 is subtracted from 5x²

Solve the terms within the parenthesis and has exponents. Group like terms and simplify.

(2x-3)(2x-3) ⇒ 2x(2x-3) -3(2x-3) ⇒ 4x² - 6x - 6x² + 9 ⇒ -2x² - 6x + 9

Deduct 3 from the answer of the previous solution.
-2x² - 6x + 9 - 3 ⇒ -2x² - 6x + 6

Deduct the answer of the previous solution from 5x²

5x² - 2x² - 6x + 6 ⇒ 3x² - 6x + 6 

3x² - 6x + 6 can be factored by 3.

3(x² - 2x + 2)

Which variable is most important to the following problem?A tentmaker has 60,000 tents in stock. The Army decides to order 350 tents
for each of its 200 brigades. Will the tentmaker have enough tents in stock?
O A. the price of one tent
O B. the number of tents the Army orders
C. the size of each tent

Answers

Answer:

B.) the number of tents the army orders

Step-by-step explanation:

The word problem does not speak of any prices or tent sizes so it cant be A or C

Answer:

its B

Step-by-step explanation:

9|-k|=14 absolute value

Answers

I hope this helps? And hope you can read cursive.

A farmer harvested 35 arces of corn. Animals ate 1/8 of the corn he orginally planted. How many arces of corn did the farmer plant?

Answers

The farmer planted 39.37 acres of corn because 1/8 of 35 is 4.37, and if you add the amount he harvested to the amount the animals ate, you get 39.37 acres of corn originally planted.

How many solutions does this system have?Y = x + 5
Y = -5x – 1
A) One
B) None
C) Infinite
D) Two

Answers

Well this does take some work on scratch paper but ill let you know that we have to plug these in to make one whole big equation 
lets do that!
x + 5 = -5x - 1 now add +1 to both sides of the equation 
   + 1 =       +1 it cancels out on the right side and we solve on the left 
*****************
x + 6 = -5x  Now lets subtract that(1x) from both sides 
-1x    = -1x ( if x stands alone, theres always an imaginary 1 right by it)
**************  now -5 - 1 = -6 so its -6x 
 6     =  -6x  Now divide both sides by -6 to isolate x to be alone 
÷-6   =  ÷6  It cancels out on the right side and we solve on the left
************ 6 ÷ -6 = 0  so lets see what we have 
 0    =   x 
Since zero is still a number this means there is only 1 solution!
Answer = A.) one 
I hope this helps! 
and dont forget 2 
MARK ME BRIANLIEST! 
=)

HEEEEEELP

question in the attached picture

Answers

1) x^(2) +2x-10=0
a=1
b=2
c=-10
x= \frac{-(2) +or-  \sqrt{ 2^(2)+4(1)(-10) } }{2(1)}
x= (-2 + or - √(4+40) )/(2)
x= (-2 +or- √(44) )/(2)
x= (-2+or- 2√(11) )/(2)
x= -1+or- √(11)
√(11)=3.32
-1+3.32 = 2.32
-1-3.32 = -4.32

2) 
x^(2) -2x-9=0
a=1
b=-2
c=-9
x= \frac{-(-2)+or- \sqrt{ (-2)^(2)+4(1)(-9) } }{2(1)}
x= (2+or- √(4+36) )/(2)
x= (2+or- √(40) )/(2)
x= (2+or-2 √(10) )/(2)
x=1+or- √(10)
√(10) =3.16
1+3.16 = 4.16
1-3.16 = -2.16

3) 
x^(2) -9x+5=0
a=1
b=-9
c=5
x= \frac{-(-9)+or- \sqrt{(-9)^(2)-4(1)(5) } }{2}
x= (9+or- √(81-20) )/(2)
x= (9+or- √(61) )/(2)
x= (9)/(2) +or-  ( √(61) )/(2)
√(61) = 7.81
(7.81)/(2) =3.91
(9)/(2)=4.5
4.5+3.91 = 8.41
4.5-3.91 = 0.59